Studies On The Effect Of Drying Modes On Quality Of Dehydrated Cabbage - Sakhale, B. K; Pawar, V. N (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2007)
An investigation was carried out for justify the suitability of various dehydration techniques for desired quality of finished products. The cabbage (brassica oleracea L. Var. Capitata), one of the commonly consumed green leafy vegetables was assessed fot its commercial processing potential through dehydration technology. The fresh cabbage procured from commercial growing farms near aurangabad city were washed, chopped into strips of uniform size and subjected to hot water blanching containing 2.0 percent common salt. The pretreated cabbage were dehydrated under different during conditions i.e. sun, shade and tray drying to safe moisture level. The dried sample were evaluated for their dehydration process features, nutritional and sensorial characteristics. The data on the dehydration technology revealed that tray dried cabbage found comparatively more wholesome, palatable and reported maximum retention of nutrients like vitamin C (42.9%), calcium (87.2%), iron (83.3%) coupled with superior dehydration and rehydration ratios and processing characteristics. The tray dried cabbage method was found comparatively superior in retention of sensorial quality features (appearance, color and overall acceptability) over sun drying and at par with shade drying. Key words: cabbage; dehydration ;pretreatment ;rehydration ;sensorial quality